Proposition d’une stratégie alternative pour massifier la rénovation en France : la mise en concession de lots d’immeubles - Benoît Schmaltz; Jonathan Villot (Développement Durable et Territoires)
This article examines and attempts to define the contours of an alternative strategy for the mass energy renovation of buildings. The aim is to address the structural conditions required for a public policy that will enable France to meet its official commitments and address its energy and climate challenges. The proposal focuses on the creation of baskets of renovation projects and the awarding of concessions to building contractors who, as concessionaires, are placed under the control of the concession authorities to ensure effective, coordinated management of the national objectives. The arguments put forward demonstrate the relevance of a new organisation of action and coordination of the actors involved in energy renovation by the public sector, with constant resources and within an established legal framework.